2013
DOI: 10.3390/agriculture3030484
|View full text |Cite
|
Sign up to set email alerts
|

Global Change and Helminth Infections in Grazing Ruminants in Europe: Impacts, Trends and Sustainable Solutions

Abstract: Infections with parasitic helminths (nematodes and trematodes) represent a significant economic and welfare burden to the global ruminant livestock industry. The increasing prevalence of anthelmintic resistance means that current control programmes are costly and unsustainable in the long term. Recent changes in the epidemiology, seasonality and geographic distribution of helminth infections have been attributed to climate change. However, other changes in environment (e.g., land use) and in livestock farming,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 91 publications
(101 reference statements)
1
74
0
Order By: Relevance
“…Haemonchus, Ostertagia, Teladorsagia, Trichostrongylus, Cooperia, Oesophagostomum, Chabertia) -continue to cause significant economic and welfare burden to the global livestock industry in Europe (Morgan et al, 2013;Charlier et al, 2014;. The ranking of these GI parasitic worms as one of the top causes of lost productivity in ruminants (http://www.discontools.eu) reinforces the increasing consideration in the European Union (EU) of the impact of strongyles upon animal health and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Haemonchus, Ostertagia, Teladorsagia, Trichostrongylus, Cooperia, Oesophagostomum, Chabertia) -continue to cause significant economic and welfare burden to the global livestock industry in Europe (Morgan et al, 2013;Charlier et al, 2014;. The ranking of these GI parasitic worms as one of the top causes of lost productivity in ruminants (http://www.discontools.eu) reinforces the increasing consideration in the European Union (EU) of the impact of strongyles upon animal health and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the answers on the two questionnaires indicated that over the years (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) the preventive measure of mowing pasture before grazing was less frequently applied and the length of the grazing season increased. All these changes are known to contribute to higher levels of GI nematode exposure (Bennema et al, 2010;Vanderstichel et al, 2012;Morgan et al, 2013). In Group 1, the level of exposure to infection was found to be positively correlated to pasture per 100 l milk and to the ratio 'dairy cow/variable cost' and negatively to the ratio 'concentrates/pasture' and 'concentrates/dairy cow' (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In literature, most studies assess the impact of GI nematodes on partial productivity measures such as milk production per cow (Charlier et al, 2009;Blanco-Penedo et al, 2012), daily weight gain (Dimander et al, 2003) and reproductive performance (Sanchez and Dohoo, 2002;Sithole et al, 2006). However, analysing the effect of GI nematodes and control measures on the whole-farm performance requires a more integrative approach (Morgan et al, 2013;van der Voort et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesised, that parasitic infections increase greenhouse gas emissions from livestock production because of the increased time and inputs required for animals to reach final production weight (Morgan et al, 2013). However, currently very little data are available on the role of endemic parasitic disease in greenhouse gas emissions or on the effect of mitigation strategies in reducing emissions.…”
Section: Applying the Framework To Coccidiosis In Broilersmentioning
confidence: 99%